Introduction geographic information system - Chang, Kang-Tsung (McGraw-Hill, 2012)
Provides students in a first or second GIS course with a foundation in both GIS concepts and the use of GIS. This title presents GIS terms and concepts and helps students learn how each one fits into a complete GIS system